Chinese Household Registration Data of Wudu County (Gansu Province), 1947 (Volume 1) : Text and Data - Li, Minghui, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
This book offers a unique dataset of the 1947 household register of the Wudu County (Gansu Province) in China. It also includes preliminary analyses of occupation, education, marriage, and the distribution of wealth in the villages of Wudu. These analyses, based on the available population register data, are not only of importance as they have never been published before, but also because they reveal various socio-economic features of villagers' lives on the individual level. They thus enable readers of this book to ask innovative questions and address them, contributing to the literature on the historical development of Chinese demography. This is Part 1 of a 3-volume set.